Book Review. Székedi Levente’s Limitele supraviețuirii: Sociologia maghiară din Transilvania după 1945 (Papers in Arts and Humanities, 2022)
The recent publication of the volume Limitele supraviețuirii. Sociologia maghiară din Transilvania după 1945 [The Limits of Survival: Hungarian Sociology in Transylvania After 1945], signed by Székedi Levente, is a notable contribution to the study of the Transylvanian Hungarian sociology, the author’s playground being, for the time being, little frequented by other researchers. The analysis of the post-1945 period, made “on the grassroots,” from the perspective of survival, focusing on sociologists such as József Venczel or Lajos Jordáky, as well as other intellectuals, makes the reader part of a stage of adaptation and transformation of the Transylvanian Hungarian sociology in the context of an austere regime. After 1948, when sociology was eliminated as a science, we are the spectators of a long process of sociologists’ resistance and disguise of sociological research, under the umbrella of institutions other than sociological ones. The “escape directions” covered areas such as: political economy, folklore, history, social history, linguistics. The reappearance of Korunk magazine in 1957 led “cautiously” to the rehabilitation of sociology in the Hungarian culture in Romania. The author of the volume emphasizes the importance of the magazine’s editor-in-chief, Professor Ernő Gáll, in this whole process of re-establishing sociology and the Gusti School, analyzing the first articles, true professions of faith that stage the new action plans and research. The volume Limitele supraviețuirii. Sociologia maghiară din Transilvania după 1945 is about the Hungarian sociology of Transylvania in the complicated historical chapters of the period after August 23rd, 1944, for two decades, while at the same time frankly addressing the situation of the Hungarian minority in Transylvania. In this sense, it is worth mentioning the multidisciplinary and dynamic character of the work, necessary for any effort of political, historical, and sociological understanding of that era.
Keywords: The Gusti School; survival; escape directions; Hungarian sociology; Ernő Gáll